Analysis Of The Relationship Of Work Environment To Employee Performance BPJS Employment Jambi - Cindy Shelomita; Irgi Sahrinra; Ratih Kusumastuti (Pusat Riset dan Inovasi Nasional, 2024)
This study aims to evaluate the work environment and employee performance at BPJS Employment in Kota Jambi, emphasizing the influence of the work environment on employee performance. Utilizing a quantitative descriptive method, the authors clarify objectives, plan the approach, and collect data for comparison between work environment conditions and employee performance. BPJS Employment in Kota Jambi, functioning as a government institution and Social Security program, is dedicated to providing community services with a commitment to excellence. The study identifies a positive relationship between the work environment and employee performance, with a regression coefficient of 0.949 indicating a potential 94.9% increase in performance with a 1% improvement in the work environment. The research confirms a significant impact of the work environment on employee performance, accounting for 76,7% of the variance, while the remaining 23.3% is influenced by unexplored variables.